Borrowing Words in an Online News - Martiarini, Elyza; Candra, Eva Nurul; Lestari, Asti Ramadhani Endah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2025)
This study aims at analyzing borrowing words in an online newspaper, namely CNN, and to identify the types of borrowing words in it. The method works in this study is descriptive qualitative in analyzing three educational rubrics at CNN. On the basis of result of the study, there are 15,70 % of three educational rubrics online news use loan words and 84,30 % use loan blends words. In addition, there is no shift in the use of loan words in the rubrics. Loan blends consisted of instrumen, prioritas, and akses. Loan blends consisted of internet, modul and total. Cultural borrowing are words that duplicate elements that the recipient language already has in its word store. They are gratuitous- by definition, another layer on the cake, because the recipient language always has viable equivalents. This result shows that the most used loan words in education rubrics are loan word combinations and the least used are loan words.